A comprehensive and in-depth analysis of the synthesis of advanced adsorbent materials. (1st September 2018) - Osuna, Francisco J.; Cota, Agustín; Pavón, Esperanza; Alba, María D.
Abstract: Na-Mica-4, a synthetic fluorophlogopite, is an attractive adsorbent. However, the synthesis at large scale demands an economically prized, feasible scalable and sustainable synthesis method, which requires a deep knowledge of the influence of each synthesis step. A set of Na-Mica-4 were synthesized by methods that had one synthesis parameter as variable. The purity, crystallinity and heteroatoms distribution were analysed thorough X-ray diffraction and nuclear magnetic resonance. The results shed a light on the main factors for the design of the final product and indicated that an environmental friendship synthesis could be possible. Graphical abstract: Image 1 Highlights: Sustainable synthesis of high charged mica is possible. A first approach to industrial scale synthesis of mica has been obtained. Natural raw materials has been used to synthesized enhanced adsorbents materials.